Female Agency in an Invented Middle Ages: Women’s Power in Westeros from an Interdisciplinary Point of View (KULT_online, 2021)
The internationally released book series A Song of Ice and Fire by fantasy author George R. R. Martin and the TV-series adaption Game of Thrones by the US-American broadcast channel HBO serve as objects of investigation for historical cultural studies. In this edited volume, the question of queenship and female agency is raised by investigating these invented Middle Ages from an interdisciplinary focus. This study of female rulers acting in an imaginary Middle Ages – and early modern history – can serve as a recommendation to introduce courtly and gender studies.